Etika Profesi dalam Pelayanan Medik: Analisis Konflik dan Implikasi Hukum Kesehatan Kontemporer - Ayu Chairun Nisa (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
A doctor is obliged to provide medical care with more in-depth and comprehensive attention in accordance with applicable medical professional standards. Doctors have the authority to perform certain medical actions based on medical law, while nurses are individuals who are trained as paramedics in caring for patients, such as anesthesiologists or intensive care specialists. From what we have explained in the discussion above, we can conclude that a medical dispute is a dispute that occurs between patients and medical personnel or health facilities, which is generally caused by patient dissatisfaction with the quality of services received or due to adverse effects experienced on their health. This conflict can arise before, during, or after medical treatment is carried out. Resolution of medical disputes can be done through legal processes or ethical resolution. The author uses a data approach in this study through library research, with data collection techniques that involve searching for relevant documents, such as journals, books, articles, and other materials. In addition, information from electronic and print media related to the topic discussed is also used as part of the data source.